PLANTING SEEDS THROUGH INDIGENOUS PEDAGOGY:: PICKING UP THE RECONCILIATION BUNDLE IN THE ACADEMY (Canadian Journal of Native Studies, 2026)
Ontario Tech University is both small in student size andyoung in relation to the Canadian academic landscape. Withits emphasis on technology well established, the university isshifting some of its attention to address the need to includeIndigenous knowledge and history through course offerings.This paper illustrates contextual details of the university, theprocess of the first Indigenous Studies course creation, andour work in listening to the stories of the students. We explorethe demographics and history of Ontario Tech University andDurham Region, where it is situated. We describe the formationof the community group that created the course, andreview our methodology addressing Indigenist research andIndigenous pedagogical approaches. We include some of theconversations we had during the writing of this paper, demonstratinglayers of story and relationality. Finally, we concludewith a discussion of the stories shared by the students, notingsome of the signs for hope and for caution.